Levels of circulating homocysteine, vitamin B6, vitamin B12, and folate in different types of open-angle glaucoma - Turgut, Burak; Kaya, Murat; Arslan, Sermal; Demir, Tamer; Guler, Mete; Kaya, Mehmet Kaan (Dove Medical Press Ltd, 2010)
Objective: To compare the levels of plasma homocysteine (Hcy), vitamin B6 (vit-B6), serum vitamin B12 (vit-B12), and folate in healthy individuals and in patients with normal tension glaucoma (NTG), pseudoexfoliative glaucoma (PXG), or primary open-angle glaucoma (POAG). Study design: A prospective controlled trial. Participants and methods: Forty healthy subjects, 48 patients with NTG, 38 patients with PXG, and 34 patients with POAG were included in the study. Those who used vitamin supplements or medications affecting Hcy and vitamin levels were excluded from the study. The levels of Hcy and vit-B6 were measured by High Performance Liquid Chromatography (HPLC). The levels of serum vit-B12 and folic acid were measured by competitive chemiluminescent enzyme immunoassay (CEI). One-way analysis if variance (ANOVA), analysis of covariance (ANCOVA), and the Tukey honestly significant difference test were used for statistical analysis. Results: The mean Hcy level of the PXG group was 15.46 +/- 9.27 mu mol/L which was significantly higher (P = 0.03) than that of the control group. There were no statistical differences in serum vit-B12 and folate levels among control subjects and NTG, PXG and POAG groups (P > 0.05). It was found that the mean plasma vit-B6 level was significantly higher in subjects with NTG (P = 0.03) and POAG (P = 0.025) versus controls. Mean vit-B6 levels in NTG and POAG were 30.50 +/- 11.29 mu g/L and 30 +/- 12.15 mu g/L, respectively. Conclusions: The plasma level of Hcy was found to be increased only in PXG patients and the plasma levels of vit-B6 were found to increase in the NTG and POAG sample groups. Using homocysteine and vit-B6 levels as the determinants of hyperhomocysteinemia still needs further research.
Keywords: normal tension glaucoma; pseudoexfoliative glaucoma; primary open-angle glaucoma; homocysteine; vitamin B6